HIPERTENSI DAN TERAPI SENAM PADA LANSIA DI BALAI POSYANDU PUNGGUR KAVLING BARU KECAMATAN NONGSA - Ditte Ayu Suntara; Afif D Alba, Fasida Dharma Yudastoro, Dedi Fatrida (Adiba Aisha Amira, 2024)
A person is considered elderly if they have reached the age of 60 years or more. Elderly people will undergo a degenerative aging process, one of the changes that occurs in elderly people is in the cardiovascular system. Changes that occur in the heart of older people include thickening of the left ventricular wall and reduced elasticity of the heart muscle. This has an impact on the blood vessels of older people who are susceptible to hypertension. One way to overcome this problem is to do tera exercises as a non- pharmacological therapy. Tera gymnastics is a combination of breathing exercises and body movements. This counseling aims to determine the impact of tera exercise on reducing blood pressure in elderly people suffering from hypertension at the Posyandu Hall, Punggur RW 17 Plot, Nongsa District. This counseling uses a quasi-experimental design with a one group pretest – posttest design. There were 25 elderly people who were respondents in this counseling